New views on PII signaling: from nitrogen sensing to global metabolic control. Issue 8 (August 2022) - Forchhammer, Karl; Selim, Khaled A.; Huergo, Luciano F.
Abstract : PII proteins are multitasking information-processing proteins occurring in bacteria, archaea, and plastids, decoding the metabolic state of the cells and providing this information to various regulatory targets. Research in recent years identified a wide range of novel PII targets mainly through ligand fishing assays, indicating that PII proteins evolved into major regulatory hubs of cellular metabolism. PII proteins orchestrate not only key steps of nitrogen and carbon metabolism but rather control a wide range of transporters and can also regulate the production of signaling molecules (c-di-GMP) and cofactors (NAD + ). A recently identified class of PII-interacting proteins, which by themselves have no enzymatic activity, modulate cellular processes through protein interactions, further extending the regulatory range of PII proteins. Highlights: PII proteins are multitasking, information-processing proteins found in all domains of life that decode the metabolic state of the cells and transduce this information to various regulatory targets. PII proteins are major regulatory hubs of cellular metabolism and orchestrate key steps of nitrogen and carbon metabolism to ensure a balanced flow of metabolites for cell growth. A range of different transporters have been recently identified as new PII targets, along with enzymes of primary metabolism, as well as enzymes required for oxaloacetate and NAD-cofactor synthesis and the synthesis of the signaling molecule (c-di-GMP). A novel class of PII-interactors occurs in cyanobacteria and archaea: small proteins without enzymatic activity that modulate cellular processes through a network of protein interactions to extend further the regulatory range of PII proteins. Understanding the mechanism of PII signal perception and transduction has allowed the development of novel in vivo metabolite-status sensors. Targeted mutations in the PII-signaling network can be used in synthetic biology to direct metabolic fluxes in desired directions for improved metabolic engineering.